Low rate of initiation and short duration of breastfeeding in a maternal and infant home visiting project targeting rural, Southern, African American women - Jessica L. Thomson; Lisa M. Tussing-Humphreys; Melissa H. Goodman; Alicia S. Landry; Sarah E. Olender (BMC, 2017)
Abstract Background Despite the benefits of breastfeeding for both infant and mother, rates in the United States remain below Healthy People 2020 breastfeeding objectives. This paper describes breastfeeding outcomes of the Delta Healthy Sprouts participants during gestational and postnatal periods. Of specific interest was whether breastfeeding intent, knowledge, and beliefs changed from the early to late gestational period. Additionally, analyses were conducted to test for associations between breastfeeding initiation and breastfeeding intent, knowledge and beliefs as well as sociodemographic characteristics and other health measures. Methods Eighty-two pregnant women were enrolled in this project spanning three Mississippi counties. Participants were randomly assigned to one of two treatment groups. Because both groups received information about breastfeeding, breastfeeding outcomes were analyzed without regard to treatment assignment. Hence participants were classified into two groups, those that initiated breastfeeding and those that did not initiate breastfeeding. Generalized linear mixed models were used to test for significant group, time, and group by time effects on breastfeeding outcomes. Results Breastfeeding knowledge scores increased significantly from baseline to late gestational period for both groups. Across time, breastfeeding belief scores were higher for the group that initiated breastfeeding as compared to the group that did not breastfeed. Only 39% (21 of 54) of participants initiated breastfeeding. Further, only one participant breastfed her infant for at least six months. Breastfeeding intent and beliefs as well as pre-pregnancy weight class significantly predicted breastfeeding initiation. Conclusions Our findings indicate that increasing knowledge about and addressing barriers for breastfeeding were insufficient to empower rural, Southern, primarily African American women to initiate or continue breastfeeding their infants. Improving breastfeeding outcomes for all socioeconomic groups will require consistent, engaging, culturally relevant education that positively influences beliefs as well as social and environmental supports that make breastfeeding the more accepted, convenient, and economical choice for infant feeding. Trial Registration clinicaltrials.gov NCT01746394 . Registered 5 December 2012.